2016
DOI: 10.2174/1381612822666160216150812
|View full text |Cite
|
Sign up to set email alerts
|

Smell and Taste Disorders Resulting from Cancer and Chemotherapy

Abstract: Malnutrition is common in both adult and pediatric patients undergoing treatment for cancer. Patients commonly attribute difficulties maintaining food intake to an altered taste developed during treatment. This review summarizes what is known about taste and smell dysfunction in patients with undergoing chemotherapy as their main treatment modality. Self-reported taste and smell alterations are prevalent in upwards of 86% of cancer patients. There is some evidence for decreased taste sensitivity in cancer pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 0 publications
1
45
0
4
Order By: Relevance
“…The recommendations stemming from prior studies that more attention be given to appetite and taste changes, which have been found to be problematic for both patients and caregivers (Bennion & Molassiotis, 2013;Cohen, Wakefield, & Laing, 2016), are consistent with our findings. Our findings also support other studies that have revealed that constipation, nausea and vomiting interfere with cancer patients' lives in significant ways, affect their adherence to medication and cause psychological distress (Dhingra et al, 2013;Salihah, Mazlan, & Lua, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…The recommendations stemming from prior studies that more attention be given to appetite and taste changes, which have been found to be problematic for both patients and caregivers (Bennion & Molassiotis, 2013;Cohen, Wakefield, & Laing, 2016), are consistent with our findings. Our findings also support other studies that have revealed that constipation, nausea and vomiting interfere with cancer patients' lives in significant ways, affect their adherence to medication and cause psychological distress (Dhingra et al, 2013;Salihah, Mazlan, & Lua, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, asthma was a predictor of poor olfactory function in patients with chronic rhinosinusitis 37. Some clinical studies have also demonstrated that smell function is significantly decreased in patients receiving cancer chemotherapy,38 39 and at least one study suggest that the prevalence of self-reported taste and smell alterations could reach as high as 86% 40. Of note, smoking was not associated with the prevalence of smell impairment in our cross-sectional analysis.…”
Section: Discussionmentioning
confidence: 41%
“…К сожалению, удаление зонда не решило в достаточной степени проблем с аппетитом и питанием ребенка обычным путем. Вопрос о решении подобной проблемы у таких пациентов до настоящего дня остается открытым и, судя по всему, требует комплексного, в том числе психологического и возможно, психиатрического, вмешательства [12,14,15].…”
Section: Discussionunclassified